Development of a simple screening test for sarcopenia in older adults. (February 2014) - Ishii, Shinya; Tanaka, Tomoki; Shibasaki, Koji; Ouchi, Yasuyoshi; Kikutani, Takeshi; Higashiguchi, Takashi; Obuchi, Shuichi P; Ishikawa‐Takata, Kazuko; Hirano, Hirohiko; Kawai, Hisashi; Tsuji, Tetsuo; Iijima, Katsuya
Abstract : Aim: To develop a simple screening test to identify older adults at high risk for sarcopenia. Methods: We studied 1971 functionally independent, community‐dwelling adults aged 65 years or older randomly selected from the resident register of Kashiwa city, Chiba, Japan. Data collection was carried out between September and November 2012. Sarcopenia was defined based on low muscle mass measured by bioimpedance analysis and either low muscle strength characterized by handgrip or low physical performance characterized by slow gait speed. Results: The prevalence of sarcopenia was 14.2% in men and 22.1% in women. After the variable selection procedure, the final model to estimate the probability of sarcopenia included three variables: age, grip strength and calf circumference. The area under the receiver operating characteristic curve, a measure of discrimination, of the final model was 0.939 with 95% confidence interval (CI) of 0.918–0.958 for men, and 0.909 with 95% CI of 0.887–0.931 for women. We created a score chart for each sex based on the final model. When the sum of sensitivity and specificity was maximized, sensitivity, specificity, and positive and negative predictive values for sarcopenia were 84.9%, 88.2%, 54.4%, and 97.2% for men, 75.5%, 92.0%, 72.8%, and 93.0% for women, respectively. Conclusions: The presence of sarcopenia could be detected using three easily obtainable variables with high accuracy. The screening test we developed could help identify functionally independent older adults with sarcopenia who are good candidates for intervention.Geriatr Gerontol Int 2014; 14 (Suppl. 1): 93–101.